Development of “Deutsch Für Touristmus” Teaching Based On Livejournal Website to Improve Student Competence in Tourism - Herlina Jasa Putri Harahap; Indah Aini (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This research is a research conducted to develop teaching materials as a means of supporting teaching and learning in the classroom in order to improve the competence and skills of students in the field of tourism in particular becoming a professional tour guide (Reiseführer / in). This teaching material is used as reference material and guidance by students in learning the Deutsch Fuer Touristmus. This study uses a development research approach using the ADDIE model conducted at the Unimed German Language Education Program. The object of this research is the development of Deutsch Für Touristmus course teaching materials. The data collection technique is used to collect data through observation, interviews and questionnaires and tests, while data analysis techniques are done using qualitative descriptive analysis, and testing of teaching materials is carried out in small groups and large groups. The results of the expert material assessment obtained values from the aspect of content worthiness of 91.67 which were categorized as very feasible, from the specs of Livejournal-based teaching materials on teaching materials included in the feasible category with a value of 80, from the aspect of language eligibility gained a value of 95.45% which was categorized very worthy. In the aspect of presentation feasibility, the value is 83.75 which is categorized as feasible and based on data from the results of the assessment of media experts, the feasibility aspect of obtaining a value of 86.25 is categorized as feasible.